Strategies for the Preservation and Tourism Development of Traditional Villages in the Context of Rural Revitalization - Chen, Danhong; Yang, Qian (Transactions on Social Science, Education and Humanities Research, 2023)
The emergence and implementation of the national rural revitalization strategy have brought new opportunities for the protection and tourism development of traditional villages. The integration of rural traditional cultural characteristics with tourism development not only effectively protects the cultural heritage of traditional villages but also promotes the rapid development of regional tourism economy. This study aims to explore the strategy of traditional village protection and tourism development under the background of rural revitalization, elucidating the significance of traditional village protection and tourism development, the relationship between the two, and the implementation principles. Based on these understandings, an effective approach to implementing the protection and tourism development of traditional villages is proposed to promote their sustainable development.